2010
DOI: 10.5154/r.rchscfa.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Estructura Y Composición De La Vegetación Del Cañón Del Zopilote, Guerrero, México

Abstract: Se analizó el cambio en la composición y estructura de la vegetación a lo largo de un gradiente altitudinal en el Cañón del Zopilote, localizado en la cuenca del río Balsas, en Guerrero. En un intervalo de 450 a 2,800 m de altitud se colocaron 28 parcelas de muestreo, en diferentes tipos de vegetación, definidos por su fisonomía. En cada tipo de vegetación se establecieron seis parcelas de 1,000 m 2 para el muestreo de las especies arbóreas, y dentro de ellas una sub-parcela de 100 m 2 para arbustivas y dos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
(10 reference statements)
0
3
0
5
Order By: Relevance
“…Due to insufficient botanical knowledge of Balsas basin (Fernández-Nava et al 1998, Jiménez-Ramírez et al 2003, Pineda-García et al 2007) and the scarcity of quantitative studies of vegetation structure (Ávila-Sánchez et al 2010, Guízar-Nolasco et al 2010 it is difficult to analyze the floristic data originated from the research in Zoyatlan under the light of other studies. However, in a first approximation we can say that the 236 species determined for Zoyatlan represent 6.28 % of the 4,442 known for the basin (Fernández-Nava et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to insufficient botanical knowledge of Balsas basin (Fernández-Nava et al 1998, Jiménez-Ramírez et al 2003, Pineda-García et al 2007) and the scarcity of quantitative studies of vegetation structure (Ávila-Sánchez et al 2010, Guízar-Nolasco et al 2010 it is difficult to analyze the floristic data originated from the research in Zoyatlan under the light of other studies. However, in a first approximation we can say that the 236 species determined for Zoyatlan represent 6.28 % of the 4,442 known for the basin (Fernández-Nava et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies about the flora of the mid and high Balsas of the state of Guerrero, we find that our records represent 23.43 % of the total of species known for the TDFs of the municipality of E. Neri, which ranks third in diversity for the whole country (Jiménez-Ramírez et al 2003); for the zone of Papalutla our data represent 49.27 % (Martínez- Gordillo et al 1997). Considering that this type of vegetation is most common in the Balsas, but also that it stands out for its high species richness and number of endemic species (Rzedowski, 1991b, Rzedowski & Calderón 2013 The research area has 29 % of all families registered for Balsas basin (Fernández-Nava et al 1998) and between 76 and 44 % of those reported in municipalities of the state of Guerrero that are part of the Balsas center (Jiménez-Ramírez et al 2003, Ávila-Sánchez et al 2010 and high subregions (Martínez-Gordillo et al 1997, Guízar-Nolasco et al 2010. These studies point to Fabaceae, Asteraceae and Poaceae as the richest in species; this is also the case in Zoyatlan.…”
Section: Discussionmentioning
confidence: 99%
“…Este enfoque fisonómico, permitió determinar que, para el caso del occidente de México, los límites entre bosque mesófilo de montaña y bosque de Abies no son abruptos, sino continuos, y se traslapan. Varios estudios se han enfocado en analizar solo el gradiente con muestreos en cañadas, crestas, cimas, elevaciones medias y tierras bajas, encontrando diferentes comunidades vegetales, comunidades discretas y discontinuidades (Vázquez- García & Givnish 1998, Ávila-Sánchez et al 2010, Hemp 2010. Además, algunos autores han estudiado regiones grandes con condiciones climáticas y ambientales muy diferentes a lo largo de un amplio gradiente altitudinal, como en el centro de Veracruz (Williams-Linera et al 2013, Toledo-Garibaldi & Williams-Linera 2014, lo cual explica los cambios un poco más abruptos y la alta heterogeneidad encontrada en los tipos de vegetación.…”
Section: Discussionunclassified
“…These species are wider distributed in Aguascalientes and often they are present in wet ravines. For example, B. cordata is recorded in the MMF of central and northwestern Mexico, indicating secondary conditions (Ávila-Sánchez, Sánchez-González, & Catalán-Everástico, 2010;Cué-Bär et al, 2003;González-Elizondo et al, 2012). Cedrela dugesii is considered part of the tropical dry forest in the Bajio region (Calderón & Germán, 1993), but in the study area it is seen as part of oak wet forests, similar to some Cedrela odorata in some MMF of Comparing the MMF of Aguascalientes and western Mexico, the record of C. macrophyllus, G. laurifolia, F. uhdei, L. glaucescens, P. serotina, Q. candicans, Q. castanea, Q. gentryi, Q. obtusata, and at genus level of Cedrela and Clethra, suggest a moderate similarity to the floristic composition of the MMF of Durango, Nayarit, northwest and western Jalisco, and part of Michoacán.…”
Section: Barranca El Ricomentioning
confidence: 99%